2022
DOI: 10.1002/2211-5463.13498
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus influenzae Protein D antibody suppression in a multi‐component vaccine formulation

Abstract: Nontypeable Haemophilus influenzae (NTHi) has emerged as a dominant mucosal pathogen causing acute otitis media (AOM) in children, acute sinusitis in children and adults, and acute exacerbations of chronic bronchitis in adults. Consequently, there is an urgent need to develop a vaccine to protect against NTHi infection. A multi-component vaccine will be desirable to avoid emergence of strains expressing modified proteins allowing vaccine escape. Protein D (PD), outer membrane protein (OMP) 26, and Protein 6 (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Blood was also drawn at week 5. At week 5, mice were challenged by H. influenzae strains as previously described ( 26 , 39 , 40 ). No additional adjuvant was used in immunization as we recently showed that the studied lipidated proteins were self-adjuvanting ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…Blood was also drawn at week 5. At week 5, mice were challenged by H. influenzae strains as previously described ( 26 , 39 , 40 ). No additional adjuvant was used in immunization as we recently showed that the studied lipidated proteins were self-adjuvanting ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…The development of multi-protein vaccines is becoming increasingly recognized as necessary for pathogens with highly variable antigens between and within strains ( Watson et al, 2019 ). However, such formulations can lead to antigenic competition, or masking of key antigenic epitopes leading to compromised immune responses to one or more antigens ( Michel et al, 2022 ). This requires analysis of antigens and responses in animal and human trials.…”
Section: Vaccines Against Ommentioning
confidence: 99%
“…Given these observations, a vaccine formulated with HMW1/HMW2 and Hia proteins may protect against a broader range of NTHi strains. Pre-clinical studies with these proteins revealed that PD immunization with OMP26 produced lowered antibody responses against PD, however, PD immunization with P6 did not mask PD immune responses ( Michel et al, 2022 ), emphasizing the necessity of compatibility studies when combining antigens. Mice immunized with a truncated adhesin protein F (PF) showed faster clearance of NTHi infections compared to mice immunized with a control peptide ( Jalalvand et al, 2014 ).…”
Section: Vaccines Against Ommentioning
confidence: 99%
“… 128 Recombinantly expressed protein D and outer membrane protein 26 could induce a robust antibody response after vaccination as a separate vaccine in a mouse model. 129 The fusion protein of E protein and PilA also expressed certain vaccine potential against NTHi biofilm in vitro mouse models. 130 The cationic cholesterol pullulan based (cCHP) - P6 nasal vaccine in the mouse model could also induce effective protective effect in the airway mucosa.…”
Section: H Influenzae Vaccine Preventionmentioning
confidence: 99%